Burial Mounds and Mythological Landscape - Potrebica, Hrvoje (Array, 2003)
Prehistoric communities adapted their material and spiritual culture in response to changes in the environment. The landscape remains the only visible framework of the population-environment interaction. Death is manifested in a landscape in form of a burial. Burial mounds, as specific form of burials, are not just external result of a burial ritual, but they also act as landmarks, consciously transforming landscape and organizing it in a certain symbolical structure. In central Europe burial mounds usually mark members of the elite that were important and perhaps the only functional elements of the social structure and as such were considered crucial for its preservation. Such important individuals passing from social structure entered both mythological structure of the community and landscape. The burial mounds mark the place of such passage that consciously transforms physical landscape into mythological, sacred landscape. The crucial importance of such interventions for the community is reflected in the amount of invested work and communal resources. By extending the elements of their mythology into the physical landscape, a community puts a claim on that landscape. In that way burial mounds became landmarks of the continuity which is the basic category that support any territorial claim. Not only that they represent the power and glory of heroes and ancestors that in such way remain physically present in the landscape, but they also implicate the power of their current successors. In order to gain control of that landscape, any other group would have to accept those landmarks as their own, either by physical intervention or by incorporating them into their own mythological context.